2005
DOI: 10.1001/archotol.131.7.583
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Lateral Oropharyngectomy for Squamous Cell Carcinoma of the Tonsillar Region

Abstract: To describe the surgical technique for transoral lateral oropharyngectomy (TLO) and its safety, postoperative management, complications, and functional outcomes. Design: A 20-year retrospective case series review. Mean follow-up was 10 years. All but 10 patients were followed up until the fifth postoperative year or death. Setting: Academic, tertiary referral center. Patients: A total of 191 patients who underwent TLO for selected invasive squamous cell carcinoma of the tonsil and/or tonsillar fossa. Intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(123 citation statements)
references
References 21 publications
3
117
0
3
Order By: Relevance
“…Tumour size, extension and involvement of adjacent structures as well as surgeon preference dictate the surgical approach. Most tonsillar fossa tumours can be managed using a transoral approach with the aid of radiofrequency, electrocautery, CO2 LASER or robotic assistance 52,53 . Some cases may require lateral pharyngotomy approach or lip-splitting anterior mandibulotomy for mandibular swing approach.…”
Section: Oropharyngeal (Tonsillar) Cancermentioning
confidence: 99%
“…Tumour size, extension and involvement of adjacent structures as well as surgeon preference dictate the surgical approach. Most tonsillar fossa tumours can be managed using a transoral approach with the aid of radiofrequency, electrocautery, CO2 LASER or robotic assistance 52,53 . Some cases may require lateral pharyngotomy approach or lip-splitting anterior mandibulotomy for mandibular swing approach.…”
Section: Oropharyngeal (Tonsillar) Cancermentioning
confidence: 99%
“…The technique for transoral surgical removal of tonsil tumors has been described by Weinstein et al [32] and Holsinger et al [33]. The mucosa is incised at the retromolar trigone, and dissection is carried to the pterygomandibular raphe.…”
Section: Lateral Oropharyngectomy and Tonsillectomy (Video 1)mentioning
confidence: 99%
“…Advances in minimally invasive techniques have resulted in a reevaluation of the role of surgical therapy in the management of OPSCC. Early reports by Laccourreye et al [14] demonstrated the role for transoral surgery after reporting excellent outcomes with lateral pharyngectomy for tonsillar cancer. They reported a 5-year local control rate of 89.0 % for T1 cancers and 81.7 % for T2 cancers using this technique.…”
Section: Surgical Options For Treatment Of Opsccmentioning
confidence: 99%